Banking Efficiency under an Oligopoly Structure: Evidence from Indonesia’s Islamic and Conventional Banks - Yoghi Citra Pratama; Ade Ananto Terminanto (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2026)
This study investigates the relationship between market structure and banking performance in Indonesia, with a particular focus on the comparative efficiency of Islamic and conventional banks. Using concentration ratio (CR) analysis and Data Envelopment Analysis (DEA), the research evaluates efficiency levels across 51 conventional banks and 14 Islamic banks during the period 2015–2021. The findings indicate that the Indonesian banking industry operates under an oligopolistic structure, dominated by a small number of large state-owned and private conventional banks. While Islamic banks demonstrated relatively higher overall and scale efficiency, conventional banks outperformed in terms of technical efficiency. Nevertheless, the differences in efficiency between Islamic and conventional banks were found to be statistically insignificant. These results suggest that although Islamic banking in Indonesia has made progress, it still faces structural and operational challenges in competing with its conventional counterparts. The study contributes to the literature on banking efficiency by integrating market concentration measures with non-parametric efficiency analysis in a dual banking system context. The findings provide important implications for policymakers and regulators in designing strategies to enhance competitiveness, improve efficiency, and foster the sustainable growth of Islamic banking within an oligopolistic market structure.